Impact of psycho-education on care givers mental health and perceived stress of children with autism (Dhaka University Journal of Biological Sciences, 2014)
The purpose of the study was to assess the impact of psycho-education on care givers mental health and level of stress. The study attempts to increase knowledge about autism in addition to reduce stress and disturbances of mental health condition among care givers of children with autism. Pre-post design was used to assess the perceived stress and mental health condition of the participants. The control group did not receive the psycho?education session and the experimental group received the psycho-education session. During the pretest all measures were administered and in post-test session all measures were re-administered to the experimental group and the control group. During postintervention phase, a significant improvement in care givers' perceived stress and mental health condition (except severe depression) was noted in the experimental group. But condition of the care givers of the control group who did not receive psycho-education remained the same for the same variables. Results suggested that psycho-educational intervention is effective in increasing knowledge regarding the condition and in meeting the needs of the care givers of children with autism spectrum disorders.